Association between sleep duration and chronic musculoskeletal pain in US adults: a cross-sectional study - Li, Chong; Huang, Huaping; Xia, Qingjie; Zhang, Li (Frontiers in Medicine, 2024)
Background This study aims to explore the association between sleep duration and the prevalence of chronic musculoskeletal pain (CMP). Methods A cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2009–2010, which involved multiple centers across the United States. The study included 3,904 adults selected based on age and complete data availability. Demographic variables such as gender, age, race, and socioeconomic status (represented by the poverty-to-income ratio) were considered. Results Of the participants, 1,595 reported less than 7 h of sleep, 2,046 reported 7–8 h, and 263 reported more than 9 h of sleep. Short sleep duration was associated with higher odds of CMP (OR, 1.611, 95% CI: 1.224–2.120, p = 0.005). Long sleep duration also showed a higher prevalence (OR, 1.751; 95% CI, 0.923 to 3.321; p = 0.059), although this result was not statistically significant. A U-shaped relationship emerged (Effective degree of freedom (EDF) = 3.32, p < 0.001), indicating that 7 h of sleep was associated with the lowest odds of CMP. In individuals with sleep durations less than 7 h, each hour increment correlated with 22.8% reduced odds of CMP (OR, 0.772; 95% CI, 0.717–0.833; p = 0.002). Beyond 7 h, each hour increment was associated with 38.9% increased odds of CMP (OR, 1.389; 95% CI, 1.103–1.749; p = 0.049). Conclusion The findings suggest that both insufficient and excessive sleep durations are linked to a higher prevalence of CMP, highlighting the importance of optimal sleep duration for musculoskeletal health.